Long-term results of 180 consecutive patients with abdominal aortic aneurysm treated with the endurant stent graft system - Benveniste, Glen L.; Tjahjono, Richard; Cheng, Oliver; Verhagen, Hence J. M.; Böckler, Dittmar; Varcoe, Ramon L. (Annals of vascular surgery, 2020)
Background - Registry studies have shown that the Endurant stent graft is associated with low rates of all-cause and aneurysm-related mortality when used for the endovascular treatment of abdominal aortic aneurysm (AAA). However, many were limited by length of follow-up and all had a proportion of patients lost to follow-up. The aim of this study is to report results from a large, real-world experience using Endurant, utilizing methods to ensure complete ascertainment of mortality. - Methods - This study describes a large, single vascular unit experience using the Endurant stent graft in consecutive patients treated between August 2008 and March 2019. - Results - One-hundred eighty patients (mean age 76.0 ± 8.6 years; 90% male) with mean AAA diameter of 57.5 ± 10.5 mm underwent endovascular aneurysm repair (EVAR). Technical success was achieved in all cases. At median follow-up of 55.0 months (interquartile range 29.8-79.0), 51 (28.3%) patients had died. Kaplan-Meier estimate of 5-year overall survival and freedom from aneurysm-related death was 71.6% and 99.4%, respectively. Lower survival rates were observed in patients who underwent EVAR at age ≥80 years (59.2% vs. 78.3%, P < 0.01) and with aneurysm diameter ≥70 mm (55.6% vs. 73.8%, P = 0.03). Thirteen endoleaks (7.2%; 4 type 1A, 2 type 1B, 7 type 2) were observed during follow-up (mean time from implantation 8.7 ± 4.2, range 1-52 months). Eleven patients (6.1%) required secondary intervention for limb occlusion (n = 7), endoleak (n = 3), and restenosis (n = 1). Patients treated within (n = 104; 57.8%) and outside (n = 76; 42.2%) the manufacturer’s instructions for use (IFU) had similar rates of endoleak (7 [6.7%] vs. 6 [7.9%]; P = 0.76), secondary re-intervention (7 [6.7%] vs. 4 [5.3%]; P = 0.74) and overall-survival (72 [69.2%] vs. 55 [72.3%]; P = 0.46). - Conclusions - Results from this real-world study of consecutive patients treated for AAA using the Endurant stent graft demonstrate that it is safe and effective, with excellent long-term outcomes for anatomy that falls both inside and outside IFU recommendations.
Gesehen am 15.10.2020